Stereological methods in cement-based materials technology: A survey of my research group’s activities during the past half of a century - Stroeven, Piet (Image Analysis and Stereology, 2019)
Four topics of high engineering relevance in which we were involved are introduced herein. Aggregate packing in concrete is of obvious relevance: denser packings lead to reduced cement demands, while modern developments in the (super) high performance range of cementitious materials are based on particle packing. Fiber reinforcement efficiency in concrete that we have studied extensively offers a relatively simple stereological problem for which Cauchy laid down the fundament. In the third problem of damage analysis the dispersion of small cracks in concrete is at issue. Insight into damage characteristics would be relevant in all (fracture) mechanical experiments. This topic can equally be linked to Cauchy. In both cases, the data acquisition by stereological methods is indicated. The fourth topic is of high actual relevance. It involves porosimetry in computer-simulated (virtual) cementitious materials, ultimately aiming permeability estimation. The stereological problems involved are indicated, and - again – Cauchy can be linked to finding solutions. Finally, new, mostly yet unpublished developments are indicated aiming for more economic procedures as well as improving reliability of permeability estimates by nano-packing of globules, so that ultimately this methodology could replace the laborious and expensive (and biased) experimental route.